Disentangling the effects of date, individual, and territory quality on the seasonal decline in fitness - Tomas Pärt; Jonas Knape; Matthew Low; Meit Öberg; Debora Arlt (Ecology, 2017)
The seasonal timing of reproduction is a major fitness factor in many organisms. Commonly, individual fitness declines with time in the breeding season. We investigated three suggested but rarely tested hypotheses for this seasonal fitness decline: (1) time per se (date hypothesis), (2) late breeders are of lower quality than early ones (individual quality hypothesis), and (3) late breeders are breeding at poorer territories than early breeders (territory quality hypothesis). We used Bayesian variance component analyses to examine reproductive output (breeding success, number fledged, and number of recruits) from repeated observations of female Northern Wheatears ( Oenanthe oenanthe ) and individual territories from a 20‐yr population study. The major part of the observed seasonal decline in reproductive output seemed to be driven by date‐related effects, whereas female age and territory type (i.e., known indicators of temporary quality) contributed to a smaller degree. Other, persistent effects linked to individual and territory identity did not show any clear patterns on the seasonal decline in reproductive output. To better disentangle the quality effects (persistent and temporary) of individual and territory from effects caused by the deterioration of the environment we suggest a protocol combining experimental manipulation of breeding time with a variance–covariance partitioning method used here.